The effect of bovine colostrum supplementation on levels of secretory immunoglobulin-A (S-IgA) in saliva of elite atheletes, non-exercising controls and non-exercising older adults : a project [i.e. thesis] completed as fulfilment of the requirements of a doctoral thesis in Clinical Nutrition, Massey University, Albany Campus, New Zealand - Crooks, Christine (Massey University, 2007)
Secretory immunoglobulin-A (S-IgA) in saliva may reflect levels of immune defence at other mucosal sites. Reduced levels of salivary S-IgA have been associated with an increased risk for upper respiratory symptoms (URS) in athletes. Previously, the consumption of a nutrition supplement, bovine colostrum (BC) by distance runners, was shown to significantly increase levels of salivary S-IgA compared to baseline; however the mechanism was not known. The immunomodulatory effect of BC is investigated further in these current studies. Twenty-five swimmers (12 males [M], 13 females [F], age 14-23 years) training at an elite level, 28 lightly-exercising students (9M, 19F, age 18-27 years), and 45 healthy older adults (20M, 20F, age 65-76 years), consumed a supplement of either BC or placebo for ten weeks. Saliva samples were collected at baseline, weekly for four weeks during supplementation and post-supplementation. Blood samples were collected at baseline, monthly during supplementation and post-supplementation. No significant changes were seen in levels of S-IgA in either BC or placebo groups within any of the cohorts. There was a trend towards a significant difference in URS reportage between BC and placebo groups in the swimmers cohort, but not in the students or older adults. There was also a trend towards a difference in the number of swimmers reporting URS. Fewer numbers of swimmers consuming BC reported URS compared the placebo (P=0.062) after consuming BC for four weeks compared to those consuming the placebo. Post-exercise plasma cortisol results were significantly reduced in the BC subgroup compared to the placebo (P=0.004). These results do not support the findings of previous intervention studies investigating the immunomodulatory effect of BC in athletes. However the reduced reportage of URS, among swimmers consuming the BC supplement, suggested there was some benefit to their health. A possible explanation is that BC has impacted on non-infectious causes of URS. Growth factors present in BC may enhance intestinal repair which could be advantageous to athletes recovering from bouts of prolonged intensive exercise. The effect of gastrointestinal disturbances on local and systemic immunity may be minimised which benefits immune protection. However an inconsistent effect of BC supplementation on immune protection in athletes means further research is still required. In these studies there was no benefit to immune protection in the student or older adult cohort. Further investigation into the safety of BC for all population groups is still required.
Keywords: Bovine colostrum supplemementation; Secretory immunoglobulin-A (S-IgA); Immunology; Intestinal repair; Athletes; Older adults; Fields of Research::320000 Medical and Health Sciences::320200 Immunology